Consumer choices among service brands offering ethical attributes. Issue 15 (10th December 2019) - Bridges, Eileen; Schramm, Mary; Roy, Abhik
ABSTRACT: This research improves understanding of how consumers integrate their evaluations of ethical attributes with other service features in making brand choices. Although consumers appreciate brands they perceive to be ethical, few studies have examined what consumers are willing to give up in order to select a brand that offers specific ethical attributes, and under what conditions they might be willing to do so. To better characterize consumer choice, both compensatory and non-compensatory models are tested; findings suggest that compensatory models, which allow for tradeoffs between attributes, offer better fit. Both healthcare services and banking services are examined, to better understand consumer valuation of ethical attributes under different conditions. The assumptions are made that healthcare services are more variable and require greater interaction with front line providers and service facilities/equipment than do banking services, and findings are discussed accordingly. The results suggest that consumers value ethical attributes significantly more in banking than in healthcare, supporting the idea that services which offer low contact and hence also low variability lead consumers to a greater focus on ethical service attributes. Managerial implications are provided.